Automatizace domácího bazénu - Veselý, Vojtěch (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Česká republika patří mezi světové bazénové velmoci. Bazény jsou dnes neodmyslitelně spjaté s každým rodinným domem na vesnici i ve městě. S nimi také souvisí filtrace a ohřev vody a jejich obsluha. Práce je zaměřena na možnosti zefektivnění a automatizace obsluhy těchto zařízení a realizaci prototypu ovládací jednotky a její testování.

The Czech Republic is one of the world's pool powerhouses. Today, swimming pools are an integral part of every family home in the village and in the town. Water filtration and heating and their operation are also related to them. This work is focused on the possibilities of efficiency and automating the operation of these devices and the realization of a control unit prototype and its testing.
Automation of the home pool
Keywords: Ohřev vody; zefektivnění ohřevu; úspora energie; Water heating; efficiency of heating; energy saving